THE EFFECTIVENESS OF USING “BUSUU” IN TEACHING SPEAKING - Mesa Maesaroh; Ade Mulyadi (Universitas Islam Al-Ihya Kuningan, 2021)
This study aims to determine the effectiveness of the Busuu application on the speaking skills of students who were tested in class X SMK Darulullum Kuningan in the 2020/2021 school year. To find out whether the Busuu application is effective or not, the researcher used a pre-experiment based research that was applied in class X. The study was conducted in 3 meetings which were designed as follows: the first meeting for the pre-test, second meetings for the treatment and the last for the post-test. As a quantitative method, data analysis was carried out using a paired simple t test. The results showed that there were significant differences in students who were taught using the Busuu application as a media. The average score of the students' pre-test was 61,875. Then in the post test, the average score for the class is 73,750. In other words, the use of Busuu application media is used in teaching speaking to effective class X students.Speaking skill